A longitudinal analysis of communication traits: communication apprehension, willingness to communicate, and self-perceived communication competence - Croucher SM; Kelly S; Nguyen T; Rocker K; Yotes T; Cullinane J (Taylor and Francis Group, 2024)
This longitudinal study assessed the communication apprehension, willingness to communicate, and self-perceived communication competence for a group of participants across a 15-year span. In total, 220 of 237 participants completed the 15-year project. The data represent six time points, with data collections happening once every three years. The results show that meeting communication apprehension, dyadic communication apprehension, public communication apprehension, willingness to communicate, and self-perceived communication competence all changed across time, indicating these traditionally thought of trait-like variables behaved more as state-like characteristics. Group communication apprehension did not change over time, indicating it may be more trait-like than state like. Results are limited by evidence of poor temporal stability for the public communication apprehension, self-perceived communication competence, and willingness to communicate measures.
Keywords: Communication apprehension; willingness to communicate; self-perceived communication competence; trait; state; reliability; temporal stability